What Drives Student Passion for French in Indonesian High Schools? - Selpiana Marischa; Pavel Kharisma Ramadhanita (WISE Pendidikan Indonesia, 2024)
This study investigates the interest of students in learning French as part of the extracurricular foreign language program at SMA Muhammadiyah 1 Metro. Utilizing a quantitative approach with a survey method, data were collected from 25 students through a Likert-scale questionnaire covering ten key aspects influencing their interest. The results indicate that 56% of students are highly motivated, and 72% express strong liking towards learning French. Additionally, 92% of students recognize the importance of French, with 80% showing high enthusiasm and frequent use of the language. A significant 92% of students oppose the suspension of the program, reflecting its value to them. Furthermore, 68% of students find the material easy to understand, and all students express a strong desire to encourage their peers to join the program. Despite the overall positive findings, challenges remain, with 20% of students feeling less motivated, 28% less active in class, and 20% struggling with comprehension. These results suggest that while the extracurricular French program is successful in engaging students, there are areas needing improvement to enhance its effectiveness. The study provides valuable insights for the development of strategies to further support student interest and participation in learning French.